Arrhythmias and Sudden Cardiac Death in Beta-Thalassemia Major Patients: Noninvasive Diagnostic Tools and Early Markers. (30th November 2019) - Russo, Vincenzo; Melillo, Enrico; Papa, Andrea A.; Rago, Anna; Chamberland, Celeste; Nigro, Gerardo
Abstract : Beta-thalassemias are a group of inherited, autosomal recessive diseases, characterized by reduced or absent synthesis of beta-globin chains of the hemoglobin tetramer, resulting in variable phenotypes, ranging from clinically asymptomatic individuals to severe anemia. Three main forms have been described: heterozygotes, homozygotes β +, and homozygotes β °. Beta-thalassemia major ( β -TM), the most serious form, is characterized by an absent synthesis of globin chains that are essential for hemoglobin formation, causing chronic hemolytic anemia. Cardiac complications represent a leading cause of mortality in β -TM patients, although an important and progressive increase of life expectancy has been demonstrated after the introduction of chelating therapies. Iron overload is the primary factor of cardiac damage resulting in thalassemic cardiomyopathy, in which diastolic dysfunction usually happens before systolic impairment and overt heart failure (HF). Although iron-induced cardiomyopathy is slowly progressive and it usually takes several decades for clinical and laboratory features of cardiac dysfunction to manifest, arrhythmias or sudden death may be present without signs of cardiac disease and only if myocardial siderosis is present. Careful analysis of electrocardiograms and other diagnostic tools may help in early identification of high-risk β -TM patients for arrhythmias and sudden cardiac death.